The Role of Workload and Work Motivation in Shaping Employee Performance in Public Infrastructure Organizations in the Electricity Transmission Sector - Zulfahmi, Zulfahmi; Pratama, Aryan Agus; Febisatria, Andhi; Zarazwanty R. Laega, Eureka Try; Sipayung, Leonardo Davidsi (Business Management, 2026)
Employee performance is a key factor in the success of public infrastructure organizations, particularly in the electricity transmission sector, which operates in a high-risk and highly regulated environment. This study aims to analyze the role of workload and work motivation in shaping employee performance in public infrastructure organizations in the electricity transmission sector. The study uses a quantitative approach with a causality design and was conducted at PT PLN's Makassar Transmission Implementation Unit. Data were collected through questionnaires administered to 60 permanent employees selected using purposive sampling. Data analysis was performed using multiple linear regression preceded by validity, reliability, and classical assumption tests. The results show that workload and work motivation each have a positive and significant effect on employee performance. In addition, these two variables simultaneously have a significant influence, explaining 57.4% of the variation in employee performance. These findings indicate that in the context of an electricity transmission organization as a high-reliability public organization, a proportionally managed workload supported by adequate work motivation can encourage improved employee performance. This study provides empirical contributions in clarifying the mechanism of employee performance formation in the electricity sector and serves as a basis for more effective human resource management in public infrastructure organizations.